Customer Care Service Management is Moving Forward to Achieve Sustainable Customer Retention in Every Industry. Does it play a Role to Increase Brand Retention? (International Journal of Management and Sustainability, 2019)
To increase the sustainable brand retention level of consumer, service quality plays a key role as the first consideration in the service or manufacturing industry. Our study reveals that consumer-friendly customer-care service is the only prime factor to grab higher brand retention at a competitive level. The study findings show that individuals having experience of customer-care service has a positive relationship with the study variable (brand retention interest) at a significant level. We also found significant correlation between using a product or service and the brand retention interest of consumer. Companies operating in either service industry or manufacturing industry focus on upper-grade customer-care service but actually deliver semi-grade services to customers especially those living in developing countries. Having such a practicable technique, the service delivery process remained the same, instead of continuous flexi development except for some developed countries like Japan and Malaysia. Therefore, the consumer gets excellent experience in developed countries and poor experience in underdeveloped or developing countries and retention interest of the same brand slides down and is identified as a strategic customer service gap by this study. Although we faced some unavoidable study limitations, the study findings and recommendations would be helpful especially for managers, decisions makers, and market planners to redraw implementable strategic plans for customer-care service management systems to achieve sustainable competitive advantages in the long run.